Advancing children's rights in sport: coaching, childhood agency and the participatory agenda. Issue 1 (2nd January 2022) - Lang, Melanie
ABSTRACT: The United Nations Convention on the Rights of the Child makes clear that children have the right to protection from violence and the right to be heard. There have been many developments in sports organisations' approaches to protecting children in recent years. The same cannot be said of advancing children's right to be heard. I argue this is due to how children are constructed, which is influenced by developmentalist conceptualisations of childhood. Applying ideas from the "new" sociology of childhood to a sporting context for the first time, I argue these dominant understandings lead to constructions of children as vulnerable and incompetent. This inadvertently foments protectionism and precludes adults from seeing children as rights bearers. To address this, a participatory model – Hart's ladder of participation – is suggested as a way coaches and other sport stakeholders can more effectively involve children in sport and help them fully realise their legal rights.